PEMBATASAN AKSES INTERNET SEBAGAI UPAYA CHINA MENJAGA KEAMANAN NASIONAL: THE GREAT FIREWALL OF CHINA - Zulfikar, Faisal Mufti (Department of International Relations Universitas Satya Negara Indonesia, 2023)
The Internet is a key factor in driving globalization. The internet enables people around the world to have an easier access to expand knowledge and collaborate. As such, countries seek to learn how the Internet works. However, China, which has the largest number of internet users in the world, instead created a censorship system called the Great Firewall of China. China set up the system because it saw that the Internet was formed by the values of freedom promoted by the western countries. Therefore, national security became the main factor motivating China to build the system. By using the theory of neoliberalism and the concept of national security, this research aims to explain the Great Firewall of China to protect its national security. The research method used in this research is analytical descriptive, with literature studies in place. The results of the study show that the idea of cyber sovereignty promoted by China has not only led to the implementation of a censorship system at the domestic level, but has also had an impact on the multinational company Google in China. The Great Firewall of China forced Google to leave China.